Academic Resilience During Emergency Online Learning: Student Narratives of Persistence and Wellbeing - Maila D. H. Rahiem; Husni Rahim; Marhamah Lidinia; Evi Muliyah; Ratna Faeruz; Dewi Salistina (CV FOUNDAE, 2026)
Although the acute emergency phase of COVID-19 has ended, the pandemic remains a valuable reference point for understanding how universities can sustain humane learning during disruption. This qualitative open-ended survey study aimed to examine how Indonesian university students narrated academic resilience during emergency online learning, identify the sources of coping, motivation, and support that sustained them, and explain why those narratives remain relevant for post-pandemic online and blended learning. Data were generated from three open-ended questions answered by 266 university students from several Indonesian cities during the major COVID-19 outbreak wave in Indonesia in early 2022. The responses were analyzed using reflexive thematic analysis. Four interrelated themes were developed: emotional burden did not cancel persistence; resilience was relational before it was individual; meaning, gratitude, and purpose organized endurance; and everyday care together with humane lecturer support sustained day-to-day persistence. The findings show that academic resilience is better understood not as a fixed individual trait, but as a dynamic process shaped by emotional regulation, supportive relationships, meaning-making, embodied routines, and pedagogical responsiveness in times of crisis. The study contributes a narrative-ecological account that shifts resilience support from a narrow focus on individual toughness toward relational, meaningful, and pedagogically responsive learning environments for future disruptions.